Comparison of multi-leaf collimator tracking and treatment-couch tracking during stereotactic body radiation therapy of prostate cancer. Issue 3 (December 2017) - Ehrbar, Stefanie; Schmid, Simon; Jöhl, Alexander; Klöck, Stephan; Guckenberger, Matthias; Riesterer, Oliver; Tanadini-Lang, Stephanie
Abstract: Purpose and background: Motion mitigation during prostate stereotactic body radiation therapy (SBRT) ensures optimal target coverage while reducing the risk of overdosage of nearby organs. The geometrical and dosimetrical performance of motion mitigation with the multileaf-collimator (MLC tracking) or the treatment couch (couch tracking) were compared. Material and methods: For ten prostate patients, SBRT treatment plans with integrated boosts were prepared using volumetric modulated arc technique. For the geometrical evaluation, a lead sphere at the beam isocenter was moved according to five prostate motion curves (i) without mitigation, (ii) with MLC tracking or (iii) with couch tracking. During irradiation, MV images were taken and the over-/underexposed areas were evaluated. For the dosimetrical evaluation, the plans were applied to a dosimetric phantom. Dose distributions with and without mitigation were evaluated inside the target structure and organs at risk. Results: The median over-/underexposed area was reduced significantly from 2.02 cm 2 without mitigation to 1.00 cm 2 and 0.45 cm 2 with MLC and couch tracking. Closest dosimetrical agreement to the static references was achieved with couch tracking. Conclusions: MLC and couch tracking at a conventional linear accelerator significantly improved the accuracy of prostate SBRT in the presence of motion, whereby couch tracking showed slightly better performance than MLC tracking.